Mahasiswa Islam dalam Perspektif Pendidikan Global - Nasir, Muhammad (Dinamika Ilmu: Jurnal Pendidikan, 2012)
Development of science and technology has given an impact to every aspect of this life. It has to be quickly responded by Islamic college students as the effort to cope with various problems as a result of the development. History has proven that Islamic college students have played a significant role in the life our state. They have played their role from time to time in four eras; (1) Values breaker, (2) Physical revolution, (4) Politics inside the campus, (5) Role enhancement of college students in the national development. However, Islamic college students still have to deal with various challenges in the global era related to their status as the intellectual moslem. Those challenges are classified into two perspectives. The first one is internal such as less understanding of moslem society about Islamic principles, less qualification of education, fanaticism of Islamic schools, and friction of among the Islamic community. The second one is external from non moslem community.